2021
DOI: 10.1016/j.xphs.2020.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Excipient-Induced Reversible Association of Therapeutic Peptides in Parenteral Formulations

Abstract: New classes of therapeutic peptides are being developed to prosecute biological targets which have been inaccessible to other modalities. Higher potency and longer half-life peptides have given rise to multiuse injectable formulations that enable convenient, low volume, and self-administered dosing; however, inclusion of antimicrobial preservatives to meet bactericidal requirements can impact other attributes of peptide formulations. Peptide-preservative interactions influencing solution-phase self-association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Likely, the hydrophobic interaction with m -cresol is extended to the acyl chain of the peptide. As reported in our previous study, peptide A without an acyl chain is less sensitive to the addition of m -cresol, forming detectable insoluble aggregates only at a higher PER . Further higher-order acyl-peptide A oligomers appear to form with exposure to m-cresol, which eventually develop into insoluble aggregates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Likely, the hydrophobic interaction with m -cresol is extended to the acyl chain of the peptide. As reported in our previous study, peptide A without an acyl chain is less sensitive to the addition of m -cresol, forming detectable insoluble aggregates only at a higher PER . Further higher-order acyl-peptide A oligomers appear to form with exposure to m-cresol, which eventually develop into insoluble aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study has focused on elucidating the molecular mechanism of m -cresol-induced peptide association, it is interesting to explore the different observations from titrating BA preliminarily. Our previous study has suggested the increase in turbidity and blue shift of the Trp fluorescence emission upon addition of m -cresol into the acyl-peptide A formulation, while no change in solutions containing BA was observed . In the current study, NMR results have identified site-specific interaction between m-cresol and acyl-peptide A (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations